2009
DOI: 10.1149/1.3158552
|View full text |Cite
|
Sign up to set email alerts
|

Effects of KF, NaOH, and KOH Electrolytes on Properties of Microarc-Oxidized Coatings on AZ91D Magnesium Alloy

Abstract: Oxide coatings were formed on AZ91D Mg alloy by microarc oxidation ͑MAO͒ in a sodium aluminate ͑NaAlO 2 ͒-based electrolyte, and the effects of additive electrolytes, KF, NaOH, and KOH, on the physical and chemical properties of the MAO coatings were investigated, particularly focusing on their corrosion resistance determined by potentiodynamic and potentiostatic tests. The anodizing characteristics ͑breakdown voltage and ignition time͒ and the phase, surface morphology, and thickness of the MAO coatings were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
20
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 42 publications
1
20
0
Order By: Relevance
“…The results indicated that the properties of MAO coating are related to its primary composition and structure which depend on several factors, such as the compositions of the substrate, 15,16 the electric parameters, [17][18][19] the concentration and chemical composition of electrolyte. 9,10,20 In these investigations above, polarization curve is also an important electrochemical method to evaluate corrosion behavior of magnesium alloy with MAO coating. The polarization curves obtained in above papers showed various patterns which were considered to only depend on the composition and structure of the MAO coating.…”
Section: Introductionmentioning
confidence: 99%
“…The results indicated that the properties of MAO coating are related to its primary composition and structure which depend on several factors, such as the compositions of the substrate, 15,16 the electric parameters, [17][18][19] the concentration and chemical composition of electrolyte. 9,10,20 In these investigations above, polarization curve is also an important electrochemical method to evaluate corrosion behavior of magnesium alloy with MAO coating. The polarization curves obtained in above papers showed various patterns which were considered to only depend on the composition and structure of the MAO coating.…”
Section: Introductionmentioning
confidence: 99%
“…1 However, the poor anti-causticity of magnesium alloy in harsh environment hinders its use in many applications. [2][3][4] Various technologies including alloying, surface modification, chemical conversion, electroplating, anodic oxidization, and plasma electrolytic oxidation (PEO) [5][6][7][8] have been developed for the protection of magnesium and its alloys. Among them, PEO technology is the most studied in recent years 9 because of the significant properties of the anodized film, such as good adhesion, high corrosion resistance, and hardness.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16] The PEO coatings are commonly composed of outer porous layer and inner dense layer, [16][17][18][19][20] and the corrosion resistance strongly depends on the properties of inner dense barrier layer. 17,18,[21][22][23][24][25][26][27][28][29][30][31] The chemical composition of the electrolytes is known to play a decisive role that determines the physical and chemical properties such as the phase, composition, and structural characteristics of the barrier layer. 20,22,[25][26][27][32][33][34] In the previous study, 25 the effects of additives (KF, NaOH, and KOH) in a sodium aluminate (NaAlO 2 )-based electrolyte on the physicochemical properties and corrosion characteristics of the PEO coatings on AZ91D Mg alloy were investigated.…”
mentioning
confidence: 99%
“…17,18,[21][22][23][24][25][26][27][28][29][30][31] The chemical composition of the electrolytes is known to play a decisive role that determines the physical and chemical properties such as the phase, composition, and structural characteristics of the barrier layer. 20,22,[25][26][27][32][33][34] In the previous study, 25 the effects of additives (KF, NaOH, and KOH) in a sodium aluminate (NaAlO 2 )-based electrolyte on the physicochemical properties and corrosion characteristics of the PEO coatings on AZ91D Mg alloy were investigated. The PEO coating obtained in KF-NaAlO 2 electrolyte exhibited the highest corrosion resistance, which has been attributed to the presence of considerably thick, fluoride (F)-containing inner dense barrier layer with crystalline MgAl 2 O 4 .…”
mentioning
confidence: 99%
See 1 more Smart Citation